PENGARUH CITRA PERUSAHAAN DAN KEPUASAN TERHADAP KEPERCAYAAN DAN DAMPAKNYA PADA LOYALITAS (Studi Pada Klien Asuransi Prudential Pru Vision Kabupaten Pati) - Fayumi, Ah.; Tjahjaningsih, Endang (Proceeding SENDI_U, 2015)
This study aims to determine the influence companyâs image and satisfaction with trust andits impact to clients loyalty on Prudentials insurance Pru Vision Pati. Total sample are 100respondents, by using purposive sampling method with criteria that clients have become customersof at least 3 years. Analysis of the data in this study using regression analyzing. Hypothesis testingis used t calculated at the level of significance (Î±) 5%. Where mediation test using path analysis.Result of regression analysis in this study resulted in the coefficient of determination for 0,941 orin other words the changes in loyalty can be affected by the companyâs image, satisfaction andtrust of 4,1%. The results of this study show that companyâs image positive and significant impacton clients trust, satisfaction positive and significant impact on clients trust, companyâs imagepositive and significant impact on clients loyalty, satisfaction positive and significant impact onclients loyalty, trust positive and significant impact on clients loyalty, and trust does not mediatethe influence of companyâs image and satisfaction of the clients loyalty.Keyword: Companyâs image, Satisfaction, Trust, Loyalty